Bilateral severe microphthalmia in a neonate with trisomy 8 mosaicism: A new finding. Issue 2 (11th November 2020) - Sanderson, Bevan; Leach, Courtney; Zein, Mike; Islam, Omar; MacLean, Gillian; Strube, Yi Ning J.; Guerin, Andrea
Abstract: Mosaic Trisomy 8 is a rare chromosomal abnormality estimated to occur one in 30, 000 newborns. The phenotype is highly variable and the severity does not appear to be correlated with the proportion of cells that contain the additional chromosome. Ocular involvement in Trisomy 8 mosaicism has previously been described to include corneal opacities, retinal dystrophy, coloboma, and unilateral microphthalmia. We report a case of severe bilateral microphthalmia in a neonate with Trisomy 8 mosaicism, a previously unrecognized ophthalmic manifestation.